Kajian Penerapan Elemen Desain Interior Arsitektur Modern Terhadap Kenyamanan Pengguna Perpustakaan Cikini - Putri C, Fadhilah; Aditya F, Dominikus (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Reading is an activity carried out to obtain written information so that the more information we read, the more information and knowledge we have. But unfortunately, the level of interest in reading in Indonesia is still relatively low. This can be seen from the less optimal use of the library by the community. One of the factors causing low interest in reading in Indonesia is inadequate library facilities, incomplete collection of books, and inadequate spatial atmosphere. The interior design of the library is quite important because it will improve the function and aesthetic value which will increase the comfort aspect of its users so that they feel at home in the library for long. Therefore, this study aims to analyze in more detail related to the elements in interior design which consists of 6 elements, namely layout, variation, coloring, air temperature, and lighting. The data collection technique for this research uses qualitative methods, namely by collecting data through literature, observing directly to the field, and analyzing the elements that make up the interior design that creates comfort for users of the Cikini Public Library, Jakarta.